AKAD-AKAD DALAM ASURANSI SYARIAH - Ramadhan, Taufiq (Sahaja: Journal Sharia and Humanities, 2022)
Every transaction in Islam must have a clear contract at the beginning, because it is legal or not, halal or haram will have an impact on the guidance of the Shari'a which has become the direction of religion in Islam. The concept of insurance in Islam is known as Ta'min, which is an anticipatory effort to minimize the risks that can occur to each human being in the future. The risk of every human being must be there, whether it is the risk of accidents, the risk of loss, and even the risk of loss of life / death. In order to minimize this risk, it is necessary to prepare to bear the calamities that will occur. The rapid development that occurs in the financial industry sector, both banks and non-banks, often practices that are not in line with Sharia principles, because the elements that cancel / forbid muamalah are MAGHRIB (Maysir, Gharar, and Riba). Therefore, it is very important for Muslims to know the contracts and mechanisms regarding the application of sharia insurance in line with Islamic values.